PENGARUH BRAND AWARENESS DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP MINAT PEMBELIAN / PURCHASE INTENTION - Zaini, Muhammad Taufiq; Suryadi , Nanang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The issuance of electronic information and transaction law in 2008 and copyright law in 2014 in response to cybercrimes has created the art commission phenomenon, in which illustrators claim and trade their works in cyber world. Top Haul Outfitter (T.H.O.), a new business in custom-clothing industry, was having difficulties in collecting revenues in 2021 due to low customers. The objective of this research is to analyze the effects of brand awareness and electronic word of mouth (E-WOM) on the purchase intention in the scope of art commission among the customers of T.H.O.’s products. The data of this quantitative research was harvested via questionnaires from 150 respondents who have made any art commission transaction and was analyzed in SPSS (IBM). The results of the analysis indicate the significant and positive effects of brand awareness and electronic word of mouth on the purchase intention. Therefore, in order to gain revenues from consumers, brand awareness improvement and digital information disbursement can be applied.